High-energy LHC design - Abelleira, JL; Amorim, D; Antipov, SA; Arsenyev, S; Benedikt, M; Bruce, R; Crouch, M; Fartoukh, S; Giovannozzi, M; Goddard, B; Hofer, M; Kersevan, R; et al. (IOP Publishing, 2018)
In the frame of the FCC study we are designing a 27 TeV hadron collider in the LHC tunnel, called the High Energy LHC (HE-LHC). The HE-LHC can be realized by replacing the LHC's 8.33 T niobium-titanium dipole magnets with 16 T niobium-tin magnets developed for FCC-hh. A high-quality beam available from the upgraded LHC injector complex and significant radiation damping allow achieving the challenging target values for both peak and integrated luminosity required by particle physics. Tunnel integration determines the maximum outer size of the magnet cryAPCostat. The HE-LHC arc optics maximizes the dipole filling factor and optimizes the dynamic aperture, while limiting the field strengths of quadrupoles and sextupoles. The low-beta optics for the experimental insertions features a shielded quadrupole triplet even longer than the HL-LHC's, which can support an interaction-point beta function of 25 cm, and survive an integrated luminosity above 10/ab. Other challenges include collimation and extraction. The choice of injection energy and injector is another important element, and so are various collective effects. We here report the HE-LHC design status.